Georgia Public Expenditure Review : Strategic Issues and Reform Agenda - World Bank (Washington, DC, 2014)
Generating growth and creating jobs within a sustainable fiscal framework is Georgia s biggest macroeconomic challenge. Although Georgia registered rapid growth of 5.7 percent a year during 2010-13, unemployment remains high at 15 percent. New growth companies, especially in tourism and other service sectors, did not generate enough formal or even informal employment. Fiscal policy played a crucial role in Georgia s recent growth performance with a fiscal stimulus driven post-crisis recovery which increased deficit and debt levels followed by fiscal consolidation during 2010-12 when recovery took hold. The weak execution of the budget in 2013 and policy uncertainty were largely responsible for the growth slowdown during the year. Tackling the growth and jobs agenda in Georgia will require significant investment in human and physical capital and the government has a large role to play here. Additional spending, where it is needed, should be undertaken within the fiscal consolidation agenda of the government, designed to help restore the macroeconomic buffers needed to secure stability and sustain confidence in the future. The change in government in 2012 marked a shift in fiscal policy with prioritization of recurrent social expenditures over capital spending, thereby, increasing budget rigidity. During 2012-13, the government raised the benefit levels under the targeted social assistance (TSA) and pensions and introduced universal health care (UHC). As a result, the fiscal deficit is likely to increase from 2.6 percent of gross domestic product (GDP) in 2013 to 3.7 percent in 2014. Over the medium term, an aging population and the need to improve health outcomes and coverage of the poor in social assistance programs will keep social expenditures high at more than 9 percent of GDP. The share of capital expenditures will level off, meanwhile. Such an outcome will reduce the government s flexibility in trimming current expenditures in the future.